Need to Manage the Thinking Behind the Thinking - Sandeep Gupta (International Society of Philosophy and Cosmology, 2015)
"Crisis" can be defined as a situation that is not conducive to human welfare. It can be either manmade or an act of nature. Acts of nature are beyond the control of man, whereas manmade crisis is controllable and reversible. If we let go of our modern scientific notions about the creation (macrocosm) and man, we find that the macrocosm is much larger than as perceived by science. It is a well-organized closed system having different dimensions, and man, a microcosm of the macrocosm, an open system within it. The laws of the macrocosm are fixed and unchangeable; and within the laws, there is also a law that gives man the discretion to either align with the higher laws of the macrocosm and create an internal and external environment of peace and harmony by getting rid of his "crisis" promoting tendencies (lower nature of man) viz. Desire (kama), Anger (krodh), Attachment (moha), Greed (lobha) and Ego (ahankar), or continue to live in an environment of internal and external confusion, conflict and crisis. The lower nature of man vitiates the basic law of the creation - the law of mutuality and harmony. Normally, we do not realize the implications of our lower nature; and even if we do, we justify ourselves by saying 'I know it is wrong, but since everyone is doing it, I had no option but to follow suit'. An irresponsible thought, a reflection of our personality. Our personality is driven by our mentality, and our mentality is a product of our awareness level also known as consciousness level (degree of our internal alignment with the cosmic laws) i.e. the thinking behind the thinking. The crisis that we face today is majorly manmade.It is a repercussion of leading a life dominated by our lower nature, our mentality of "I-Me-My". Since, the cause is inside us, the solution also rests within us. We need to change our mentality from the "I-Me-My" mode to the "We-Us-Ours" mode; and the only way to make it happen is to work on expanding our consciousness level i.e. 'manage our thinking behind our thinking' by leading a righteous life. In this background, this paper makes out a case that the permanent solution to all the confusion, conflict and crisis that the world is facing today, rest inside us and not outside us. Drawing from the ancient Indian text and modern mysticism, known for its scientific temper, this paper has been divided in five sections: (I) Introduction; (II) Macrocosm and its Reality; (III) Communion between Man (Microcosm) and the Macrocosm; (IV) Phenomenon of Human Consciousness (Thinking behind the Thinking); and (V) Prevailing Crisis and the Way Forward.